A Case of Thoracic SMARCA4-Deficient Undifferentiated Tumor on 18F-FDG PET/CT - Zhao, Gege; Huang, Zhongke (Nuklearmedizin - NuclearMedicine, 2024)
A 65-year-old man, who denied a smoking history, presented with chest distress and pain persisting for over a week. A contrast-enhanced chest CT scan revealed a large irregular mass in the right thoracic cavity with heterogeneous enhancement. The 18F-FDG PET/CT showed a large mass in the right thoracic cavity with heterogeneous markedly high FDG uptake. The patient subsequently underwent a bronchoscopic-guided mucosal biopsy at the opening of the right upper lobe. The histological and immunohistochemical findings were consistent with thoracic SMARCA4-deficient undifferentiated tumor.
Keywords: SMARCA4; thoracic SMARCA4-deficient undifferentiated tumor; 18F-FDG; PET/CT